Entrepreneurship Education as Part of Higher Education Reform in Egypt: An Exploratory Qualitative Case Study - Mersal, Mona (AUC Knowledge Fountain, 2022)
Higher Education plays a key role in developing societies’ economies through preparing successful leaders and citizens who can compete in today’s rapidly-changing labor market. Entrepreneurship education can pave the way for job creation, innovation, critical thinking, and economic growth. The aim of this study is to explore the views of higher education stakeholders about the economic, socio-cultural, and pedagogical implications of entrepreneurship education in a private international higher education institution in Egypt, namely the American University in Cairo (AUC). Moreover, the study seeks to investigate some of the obstacles and best practices of entrepreneurship education at the AUC. The study adopted a qualitative case study design to answer the study questions. Semi-structured one-on-one interviews were utilized to gather the required data. The purposeful sampling technique was utilized for selecting fourteen stakeholders from the AUC. Clark’s (1998) framework of the entrepreneurial university informed data collection and provided the lenses from which the study results were analyzed and interpreted. The study provides a clear picture and deep understanding of entrepreneurship education in higher education, its implementation practices and the challenges faced in one of the Egyptian international higher education institutions. The findings showed that there is a direct correlation between entrepreneurship and economic growth, innovation, and job-creation. Moreover, entrepreneurship education acts as a catalyst for tackling social issues and changing learners’ mindset to take risks, pursue opportunities, and become job-creators. The findings also revealed that although the AUC is considered as the best university that supports entrepreneurship and business ventures in Egypt, there is still a lot to be done to advance entrepreneurship at the AUC.